On the problem of the 'unnamed' in civil law - S.I. Suslovа (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
The paper considers the problem of understanding the “unnamed” in civil law, various approaches to it in accordance with the definition in legislation and civil doctrine. Examples have been given to show how the number of cases of application of the term increases in the legal literature. It has been suggested to distinguish between the concepts of “gap in law” and “unnamed”. It has been argued that they should be considered through the prism of such philosophical categories as “cause” and “consequence”. The phenomenon of qualified silence of the legislator and its relationship with the concept of “gap in law” have been analyzed. In the legal literature, the basis for their distinction is laid in the intention of the legislator. This criterion is subjective. Accordingly, a “gap in law” arises in the event of omission of the legislator, and qualified silence arises when there is a targeted law-making policy. It has been proposed to abandon the subjective criterion and the characteristics of the gap in law from the position of a positive or negative phenomenon. The “gap in law” is an objective category indicating that there is no provision in the law that would directly regulate the relationship that has arisen. Subjective and objective points matter when interpreting the rights and responding to the established paths and determining the ways to eliminate them. The choice of the directly fixed, allowable, alternative, and forbidden “unnamed” has been justified.